Church, world, and the Christian life : practical-prophetic ecclesiology - Healy, Nicholas M. (Cambridge studies in Christian doctrine., 2000)
This book analyzes the impact of pluralism and inclusivism upon ecclesiology, and draws upon Balthasar's theodramatic theory, MacIntyre's theory of traditional inquiry, postmodern critiques of humanism, and postmodern ethnography to develop a more flexible and concrete ecclesiology that can better address the practical and pastoral needs of the church.